Utilization of MODIS Surface Reflectance to Generate Air Temperature Information in East Java - Indonesia - Arif Faisol; Indarto Indarto; Elida Novita; Budiyono Budiyono (Geoplanning: Journal of Geomatics and Planning, 2020)
Ambient air temperature is main variable in climatological and hydrological analysis, however limited number of meteorological stations in Indonesia was becoming a problem to provide air temperature data for large areas.  The objective of this study is to generate air temparature using relationship of land surface temperature and vegetation index. A total of 6 climatological station and 84 MODIS Images for three years (2015 to 2017) were used for the analysis.  Research methods include: image georeferencing, band extraction from modis, derivation of NDVI, gererating ambient air temperature, calibrating using local meteorological station, and image interpretation. Results show that the accuracy of MODIS Surface Reflectance product to generate ambient air temperature in East Java at any periods is 86,37%. So MODIS Surface Reflectance product can be used as alternative solution to generate ambient air temperature.